Pathogenesis of nephro-and testiculopathies induced by the Malaysian isolate of Trypanosoma evansi in rabbits - Gumar, Yasameen Sahib (2015)
Trypanosoma evansi, the causative agent of Surra, is a severe parasitic infection of animals leading to morbidity and mortality among livestock. The pathogenesis of surra is obscured and not fully elucidated with regards to nephro-and testiculopathies along with anaemia in the chronically infected laboratory model. This forms the basis of the present investigation. This study was designed to provide partial explanation on histopathological alterations, detection and distribution of trypanosomal antigen during the progress of the disease in rabbits experimentally infected with T. evansi. Thirty five male rabbits with an average weight of approximately 2-2.3 kg were divided randomly into seven experimental groups comprising of five rabbits each. Animals from trypanosome-infected groups were inoculated intravenously (I/V) with 1×105 trypanosome/ml while the control group received phosphate saline glucose (PSG) buffer via the same route. Parasitaemia was estimated twice weekly for six months post infection (p.i.). Body temperatures were measured prior to blood sampling. The weights of the rabbits in each group were measured every 10 days. Standard haematological and biochemical parameters including Hb, PCV, RBC,WBC and differential counts were done. Five rabbits from each group were sacrificed and examined at 1, 2, 3, 4, 5 and 6 months pi. The protozoan was found in the blood of the infected rabbits as early as 72 hours p.i. Haemogram showed an obvious drop in Hb, PCV, total erythrocyte count and leucocytosis. Anaemia was followed by the first wave of parasitaemia which continued until the end of the experimental period. Differential WBC counts showed heterophilia, lymphocytopaenia, monocytosis and eosinophilia. Biochemical analysis showed a significant increase in serum levels of urea, creatinine, ALT, AST, GGT,globulin, total protein plus a decrease in albumin and glucose. At necropsy,nephropathy, hepatomegaly, splenomegaly and testiculopathy were observed. Microscopical observations in the kidney include moderate to severe tubular degeneration and necrosis, shrunken glomeruli with increase Bowman’s spaces and membranous glomerulonephritis. Amylidiosis were demonstrated at 5 and 6 months p.i. Testicular changes especially that of severe degeneration and aspermia were observed by the first month p.i. All changes were consistent with trypanosome infection and were confirmed by presence of trypanosomes in these tissues by immunohistochemistry and immunoflourescent techniques. The data denotes that the pathogenesis of Malaysian isolate of trypanosomosis in rabbit model is associated with a pronounced biochemical and morphological changes in the kidneys and testicles, in addition to chronic hematological disorders such as anaemia. The T. evansi was demonstrated by an immunohistochemical technique in formalinfixed tissues of rabbits. The immunopositive antigenic expression of T. evansi was clearly disseminated in the parietal layer of Bowman’s capsule together with glomerular capillaries; the same expression was seen in the renal interstitial of the blood vessels. In the testicles, the antigenic expression was prominent in the seminiferous tubules, in the testicular blood vessels and in the testicular interstitial connective tissue. Moreover, immunopositive reaction was seen in the epithelium lining of the epididymis. Electron microscopy showed electron-dense deposits and podocyte fusions. Also, the presence of swelling mitochondria denoting oxidative damage due to lipid peroxidation, which was visualized in the kidneys and testicles of T. evansi infected rabbits. The IgG and IgM antibody levels were elevated following infection while the C3 activation by antigen-antibody complexes during the infection also resulted in hypocomplementaemia. Cytokines such as IL-1, IL-6, TNF-α, INF-γ and IL-10 were measured and compared with the level of anaemia. Although the pathogenesis of anaemia in T. evansi infection is not obviously well-defined, the study showed that elevated levels of these cytokines together with the haematological findings may explain the pathological mechanism of T. evansi on the host with resultant organ damage and anaemia. t was concluded that rabbits intravenously injected with the Malaysian isolate of T. evansi developed end stage kidney disease and very severe testicular and epididymal damage that could result in infertility. Furthermore, rabbits play an important role as a model to study the chronic pathological effects of T. Evans which mimics the natural infection. Immunohistochemistry technique is an important diagnostic method to confirm the infection even when the parasites become undetectable in the peripheral blood.